2015
DOI: 10.1590/so100-720320150005217
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus rhamnosus pode alterar a virulência de Candida albicans

Abstract: ResumoOBJETIVO: Avaliar a influência de Lactobacillus rhamnosus na expressão dos fatores de virulência de Candida albicans in vitro. MÉTODOS: Uma suspensão de L. rhamnosus foi inicialmente cultivada em ágar MRS. No dia seguinte, foi adicionado ágar Sabouraud dextrose sobre o crescimento dos lactobacilos e C. albicans foi cultivada, por 24, 48 e 72 horas. As cepas de Candida foram então isoladas para investigação da capacidade de formação de biofilme, por meio do cultivo em placas de 96 poços e leitura das dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…The inhibition of these virulence factors in C. albicans is an important tool for the treatment of candidiasis. Several studies in the literature showed that some Lactobacillus strains were able to inhibit C. albicans through the production of bacteriocins, environmental alterations through the production and secretion of molecules arising from the metabolism of lactic acid and hydrogen peroxide, or even by mechanical inhibition of adhesion receptors (Orsi et al 2014;Leão et al 2015;Santos et al 2016;Wannun et al 2016). Probiotic bacteria are also capable of modulating the immune systems of their hosts through the production of cytokines and the stimulation of cellular activity (Mendonc ßa et al 2012;Shibasaki et al 2014;Roy et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The inhibition of these virulence factors in C. albicans is an important tool for the treatment of candidiasis. Several studies in the literature showed that some Lactobacillus strains were able to inhibit C. albicans through the production of bacteriocins, environmental alterations through the production and secretion of molecules arising from the metabolism of lactic acid and hydrogen peroxide, or even by mechanical inhibition of adhesion receptors (Orsi et al 2014;Leão et al 2015;Santos et al 2016;Wannun et al 2016). Probiotic bacteria are also capable of modulating the immune systems of their hosts through the production of cytokines and the stimulation of cellular activity (Mendonc ßa et al 2012;Shibasaki et al 2014;Roy et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A capacidade heterofermentativa facultativa possibilita à espécie utilizar pentoses para produzir ácido acético (OLIVEIRA et al, 2012). Lacticaseibacillus rhamnosus é encontrada em derivados de leite, cavidade vaginal e no trato gastrointestinal, com característica transitória neste local (REUTER, 2001, SUCCI et al, 2005LEÃO et al, 2015). Douillard et al (2013), utilizaram como comparação a cultura de L.…”
Section: Lacticaseibacillus Rhamnosusunclassified